Characterization of E-Shaped Wifi Antenna by Various Substrate - POUKIN, RAIMI; Esa, Dr Fahmiruddin (Enhanced Knowledge in Sciences and Technology, 2023)
This study aims to develop and characterize an E-shaped patch microstrip antenna design that resonates at 2.6 GHz. The design and simulation of the E-shaped patch microstrip antenna were carried out with the CST microwave studio suite. The matrix used was BUEHLER Epoxy resin and hardener with a variety of loading filler Barium strontium titanate (BST), Barium titanate (BTO), Nickel copper zink ferrite (NCZFO) of different compositions Ni0.1Cu0.4Zn0.5Fe2O4 and Ni0.3Cu0.2Zn0.5Fe2O4. the substrate design is 50×50×2 mm. The results of the five-substrate loading filler have different permittivity, it resonates at around 2.6 GHz band, S11 of -26 dB, and bandwidth 94 MHz. The resonance shift to the higher frequency when using magnetic filler, while it shifts to the lower band when using dielectric filler.